CONSTRUCTION FEATURES OF A 3D FINITE ELEMENT MODEL OF THE MANDIBULAR MOLAR SEGMENT FOR STRESSSTRAIN ANALYSIS OF THE ALVEOLAR PROCESS - Avetikov, H.D.; Plyak, O.A.; Ivanitska, O.S. (Актуальні проблеми сучасної медицини Вісник Української медичної стоматологічної академії, 2025)
Relevance. The article presents the creation and analysis of a three-dimensional finite element model of a mandibular segment with a distoangular and partially impacted third molar. The relevance of the study consists in the high prevalence of cases requiring atypical extraction of impacted third molars and the lack of personalized surgical algorithms based on biomechanical conditions. Objective. The aim of this study was to develop a computational 3D model that allows for the assessment of the stress-strain state of alveolar bone tissues and the determination of optimal parameters for cortical bone preparation during surgery. Methods. The modeling was carried out using CAD and finite element analysis (FEA) in FEMAP software. The model incorporated anatomically accurate structures of the mandible and teeth, including enamel, dentin, periodontal ligament, cortical and cancellous bone, with isotropic physical and mechanical properties assigned to each tissue type. Different depths of cortical plate preparation (0 to 1.2 mm) were simulated in the area of contact with the dental elevator. A vertical load of 10 N was applied, mimicking clinical extraction conditions. Results. The results demonstrated that in the absence of a prepared socket for the elevator, peak equivalent stresses in the cortical plate were significantly higher. The minimum stress values were recorded at a groove depth of 1.2 mm, corresponding to half the diameter of the elevator tip. This finding supports the clinical relevance of shaping the cortical bone to match the surface of the instrument in order to reduce bone compression and ensure elevator stability during luxation. Expanding the contact surface area between the instrument and bone was shown to significantly decrease local stress concentrations. Conclusion. The developed model provides a biomechanical basis for forming personalized clinical approaches to the surgical removal of lower third molars and can be used as a predictive tool for stress distribution in alveolar bone during tooth extraction procedures.